Study of piezoelectric oscillations by using a laser measuring system - Batryshev, D.G.; Akhanova, N.Е.; Yerlanuly, Ye.; Darznek, S.А. (Recent Contributions to Physics, 2020)
Today, acoustic non-destructive testing methods play an important role in the process of diagnosing the technical condition of industrial devices and facilities to ensure their safe and reliable operation. For these purposes, the so-called acoustoelectric transducers are used as a specialized tool, which is based on the conversion of mechanical displacement into an electrical signal. On the other hand, such converters are called piezoelectrics, which have to have special properties as sensitivity and reliability. Calibration and verification procedures based on optical research methods are used to ensure such technical characteristics. This work is devoted to a similar kind of research, namely, the study of oscillations of a piezoelectric using a laser measuring system operating on the principle of the A. Michelson interferometer. In the experimental works, it was found that a change in the parameters of the mechanical vibration of a ceramic piezoelectric leads to a change in the shape of the recorded signal of the photodetector (interference pattern). It is known that in the process of optical measurements there are several uncontrolled noises, and to reduce their effects, including noise from the photodetector itself, there is a need to reduce the frequency and amplitude of oscillation of the piezoelectric. It is shown that the use of calculated filtering makes it possible to isolate the useful signal and conveniently determine the dependence of the piezoelectric displacement on time.